Tindakan Supervisi dan Kepuasan Kerja Akuntan Pemula di Kantor Akuntan Publik - Myrna Nurahma', Nur Indriantoro (IAIKAP, 2000)
The Accounting Education change Commission relased its Issues Statement No.4 addressing concerns with the early employment experiences of professional accountants supervisors of entry-level staff can empply to improve job satisfaction. This study reports the results of a survey of 97 entry-level accountants from 57 local, national and Big 5 accounting firms relative to their perceptions of the exixtence of the supervisory action. This study finds that the three major elements of supervisory action recommended by the AECC, Leadership and mentoring, working conditions, and assignments are all correlated with reported job satisfaction. However, three are signifficant difference between small firms and Big 5 firms relative to both working conditions actions and job satisfaction with accountants at smaller firms reporting higher levels of each